The Contagion of Unethical Pro-organizational Behavior: From Leaders to Followers - Zhang, Yun; He, Bin; Sun, Xu (Frontiers in Psychology, 2018)
Unethical pro-organizational behavior is a common phenomenon in businesses, and one that can cause great damage to them as well as to wider society. Although prior studies have investigated why individuals engage in unethical pro-organizational behavior, little research has been undertaken into why such behavior might be commonplace in organizations. The present study focuses on the downstream contagion of unethical pro-organizational behavior from leaders to followers. Drawing on social identity theory, we consider why leaders’ unethical pro-organizational behavior brings about corresponding behavior in their employees. Moreover, we predict that leader identification and moral identity will moderate this relationship. Using a time-lag study design, we collected a sample of 227 multisource time-lagged data with which to test our hypotheses. The results show that there is a significant positive relationship between leaders’ and employees’ unethical pro-organizational behavior, and that this relationship is stronger when employees have higher leader identification and lower moral identity levels. The theoretical and practical implications of our findings are discussed in this paper, as are the limitations of the study.